Persistence of Elevated Procalcitonin in a Patient with Coronavirus Disease 2019 Uncovered a Diagnosis of Medullary Thyroid Carcinoma - Laura Gianotti, MD, PhD; Salvatore D’Agnano, MD; Giorgio Pettiti, MD; Francesco Tassone, MD; Giorgio Giraudo, MD; Corrado Lauro, MD; Giuseppe Lauria, MD; Valerio Del Bono, MD; Giorgio Borretta, MD (AACE Clinical Case Reports, 2021)
Objective: During the ongoing coronavirus disease 2019 pandemic, procalcitonin (PCT) levels have proven useful in assisting clinicians to diagnose bacterial superinfection. However, in the absence of signs of infection or at the resolution thereof, inappropriately and persistently high PCT levels may suggest and reveal the presence of other pathologies. We report a patient with severe acute respiratory syndrome coronavirus 2 pneumonia with initially elevated PCT levels that persisted during recovery, prompting the diagnosis of medullary thyroid carcinoma (MTC). Methods: A 43-year-old man presented with a 2-day history of fever, sneezing, sore throat, and dry cough. His PCT was 94 ng/mL (normal value, 0.00-0.10 ng/mL), and he was positive for severe acute respiratory syndrome coronavirus 2 RNA. Results: Empirical antibiotic therapy was administered for 7 days, but despite a clinical improvement, serum PCT remained high (84 ng/mL). Serum calcitonin (CTN) was 2120 pg/mL (normal, ≤12 pg/mL). Cytologic examination of thyroid nodules and CTN measurement of the aspiration needle washout confirmed MTC. The patient underwent total thyroidectomy with bilateral cervical lymph node dissection. Lowered CTN (986 pg/mL) and PCT (16 ng/mL) levels were observed 48 hours after surgery. A close follow-up was planned following the results of RET gene analysis. Conclusion: PCT can be a useful biochemical marker of MTC suspicion in patients with inflammatory conditions and persistently elevated PCT, even after resolution. In our case, high levels of PCT in a patient with coronavirus disease 2019 pneumonia without signs of bacterial infection led to MTC diagnosis.